Development of a sampling system for monitoring population levels of tetranychid mites (Acarina: Tetranychidae) on apple trees in the Elgin area - Pringle, K. L.(Kenneth Llewellyn) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D. Agric.) -- University of Stellenbosch, 1987.